2013
DOI: 10.3791/50178
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Respiratory Muscle Activation Using Respiratory Motor Control Assessment (RMCA) in Individuals with Chronic Spinal Cord Injury

Abstract: Short Abstract The purpose of this publication is to present our original work on a multi-muscle surface electromyographic approach to quantitatively characterize respiratory muscle activation patterns in individuals with chronic spinal cord injury using vector-based analysis. Long Abstract During breathing, activation of respiratory muscles is coordinated by integrated input from the brain, brainstem, and spinal cord. When this coordination is disrupted by spinal cord injury (SCI), control of respiratory mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 13 publications
(19 reference statements)
0
20
0
Order By: Relevance
“…sEMG input was amplified with a gain of 2000, filtered at 4–1000 Hz and sampled at 2000 Hz. The overall amount of sEMG Magnitude (μV, Mag) and the Similarity Index (SI), that quantitate the multi-muscle distribution of activation during Maximum Expiratory Pressure Task (MEPT) in COPD subject compared to that of healthy subjects were calculated using vector-based analysis as previously described (Aslan et al, 2013; Ovechkin et al, 2010). In brief: multi-muscle activity parameters were calculated using averaged sEMG amplitudes using root mean squared (RMS) algorithm from each SCI subject for comparison to group values from NI subjects.…”
Section: Methodsmentioning
confidence: 99%
“…sEMG input was amplified with a gain of 2000, filtered at 4–1000 Hz and sampled at 2000 Hz. The overall amount of sEMG Magnitude (μV, Mag) and the Similarity Index (SI), that quantitate the multi-muscle distribution of activation during Maximum Expiratory Pressure Task (MEPT) in COPD subject compared to that of healthy subjects were calculated using vector-based analysis as previously described (Aslan et al, 2013; Ovechkin et al, 2010). In brief: multi-muscle activity parameters were calculated using averaged sEMG amplitudes using root mean squared (RMS) algorithm from each SCI subject for comparison to group values from NI subjects.…”
Section: Methodsmentioning
confidence: 99%
“…However, there are no reports in the literature to indicate whether SCI would render the Valsalva maneuver difficult (Grimm et al, 1998; Johnson et al, 1969; Previnaire et al, 2012). Our previous work has shown that the majority of individuals with chronic SCI are able to generate substantial and sustained airway pressure during the MEP maneuver (Aslan et al, 2013; Ovechkin et al, 2010). …”
Section: Introductionmentioning
confidence: 99%
“…Latex-free, hypoallergenic woven tape (BSN medical) was used to secure the electrodes in place. The sEMG signals were sampled at 2000Hz and mean rectified for burst duration and root mean square values were calculated (Aslan et al, 2013). …”
Section: Methodsmentioning
confidence: 99%